Myocardial Infarction Presenting as Ear Fullness and Pain. (7th March 2018) - Ugalde, Israel; Anjum, Ibrar; Lo Presti, Saberio; Tolentino, Alfonso
Acute coronary syndrome usually presents with retrosternal chest pain, nausea, vomiting, sweating, and jaw and arm pain. Some patients only present with neck, epigastric, or ear discomfort. A 47-year-old male with a history of hypertension and coronary artery disease presented to the emergency department complaining of bilateral otalgia. He never felt chest pain, jaw pain, nausea, diaphoresis, or shortness of breath. He had a history of 2 acute coronary events and had a stress test 2 months prior to admission, which was unremarkable. The initial electrocardiography was sinus rhythm with Q-waves in the inferior leads and nonspecific ST changes in the lateral leads. His troponin on admission was normal but subsequently elevated to 20.00 mg/mL after 24 hours. He underwent left heart catheterization, which found significant occlusive disease of the second and fourth obtuse marginal branches and 2 drug-eluting stents were placed. His ear pain resolved soon after cardiac catheterization. The pathophysiology of this referred pain is thought to be related to the neuroanatomy of the nerves innervating the heart and ear. The auricular nerve branch of the vagus nerve supplies the inner portion of the external ear. Only a few cases with the complaint of otalgia have been reported. Patients were older, more frequently women, and with diabetes or heart failure. Clinicians should be aware of the atypical presentation of angina that may be life-threatening cardiac ischemia. Ear pain and fullness could be the sole presenting symptom in a patient with acute coronary syndrome.